2021
DOI: 10.1111/nana.12758
|View full text |Cite
|
Sign up to set email alerts
|

Good Minzu and bad Muslims: Islamophobia in China's state media

Abstract: Since 2014, observers of Chinese society have noted an upsurge in Islamophobic sentiment among China's ethnic majority Han. China's Muslims, in particular those who identify as Hui and Uyghur, report an increase in harassment, both online and in person. This Islamophobic backlash occurs in conjunction with retrenchments by the Chinese state on the right to practice religion. What gives rise to this increase in bigotry? This pilot study examines official discourse about Islam through an inductive analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Importantly, however, Islamophobia is not limited to the "West": anti-Muslim hostility takes place outside of North America and Europe as well. For example, from 2014 to 2018, there was an outbreak of online harassment of Muslims on Chinese platforms such as Sina Weibo and Weixin (Stroup 2021). Further research has shown that in order to construct an image of ethnic unity at home, Chinese state media have drawn stark contrasts between Islam internationally and China's Muslim minorities, framing Islam internationally as dangerous, but at the same time stripping Chinese Muslim communities of their "Muslimness".…”
Section: "Love Jihad": Sexuality Reproduction and The Construction Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, however, Islamophobia is not limited to the "West": anti-Muslim hostility takes place outside of North America and Europe as well. For example, from 2014 to 2018, there was an outbreak of online harassment of Muslims on Chinese platforms such as Sina Weibo and Weixin (Stroup 2021). Further research has shown that in order to construct an image of ethnic unity at home, Chinese state media have drawn stark contrasts between Islam internationally and China's Muslim minorities, framing Islam internationally as dangerous, but at the same time stripping Chinese Muslim communities of their "Muslimness".…”
Section: "Love Jihad": Sexuality Reproduction and The Construction Of...mentioning
confidence: 99%
“…Further research has shown that in order to construct an image of ethnic unity at home, Chinese state media have drawn stark contrasts between Islam internationally and China's Muslim minorities, framing Islam internationally as dangerous, but at the same time stripping Chinese Muslim communities of their "Muslimness". This extremely negative depiction of Islam in the global context may unintentionally give rise to popular suspicion of domestic Muslim communities (Stroup 2021). Looking to the world's largest democracy, India, the Modi era (2014-) demonstrates the power of anti-Muslim Hindu nationalist politics aiming to build a Hindu majoritarian state (Chatterji et al 2019).…”
Section: "Love Jihad": Sexuality Reproduction and The Construction Of...mentioning
confidence: 99%